ANALYSIS OF THE EFFECT OF PROFITABILITY AND SOLVENCY ON SHARE PRICES OF FOOD & BEVERAGES SECTOR COMPANIES ON THE BEI IN 2021-2022 (Prosiding dan Call Paper Widya Wiwaha, 2023)
The purpose of this research is to find out whether Profitability and Solvency either partially or simultaneously have a significant effect on the stock prices of Food and Beverages companies listed on the IDX. The data analysis method used is the classical assumption test, multiple linear regression analysis and hypothesis testing. The data used in this study is secondary data, namely by collecting data on the financial reports of Food and Beverages companies in the form of financial reports compiled from 2021 to 2022 which are listed on the Indonesia Stock Exchange. The samples used in this study were 28 samples. The results of the partial t test show that the significance level is obtained from the independent variables, namely profitability of 0.000 and the value of t is 2.073. This shows that Profitability has a significant effect on stock prices. While the significance level of Solvency is 0.002 and the t value is -1.830. This shows that Solvability has no significant effect on stock prices.
Keywords: Profitability; Solvability; Stock Price; Perusahaan Food and Beverages Company